1984
DOI: 10.1161/01.cir.69.4.703
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous measurement of left and right ventricular stroke volume and pressure-volume relationships with an impedance catheter.

Abstract: The feasibility of using continuous on-line recording of intraventricular electrical impedance to measure ventricular stroke volume was assessed in 12 patients at cardiac catheterization with a multielectrode impedance catheter and a 1.3 kHz measuring current of 4 ,A. Stroke volumes determined by electrical impedance were compared with stroke volumes determined by the thermodilution technique in 10 patients and correlated with an r value of .95. Directional changes in impedance recordings throughout the cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
2

Year Published

1987
1987
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(33 citation statements)
references
References 7 publications
1
30
0
2
Order By: Relevance
“…IVC occlusion, unlike pharmacologic loading Adjustment used in nearly all prior human studies , can be readily repeated before and after drug administration and during atrial or ventricular pacing. Although previous reports have shown some of the capabilities and safety of these techniques [ 12,15,24], demonstration of their combined use for assessment of calibrated left ventricular pressure-volume relationhips in man has not been made. Only one prior study, in animals, has shown the potential of this approach using calibrated volumes [ …”
Section: Introductionmentioning
confidence: 99%
“…IVC occlusion, unlike pharmacologic loading Adjustment used in nearly all prior human studies , can be readily repeated before and after drug administration and during atrial or ventricular pacing. Although previous reports have shown some of the capabilities and safety of these techniques [ 12,15,24], demonstration of their combined use for assessment of calibrated left ventricular pressure-volume relationhips in man has not been made. Only one prior study, in animals, has shown the potential of this approach using calibrated volumes [ …”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of ventricular systolic performance in the PV plane has been extensively performed in the adult human and dog (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). In the adult, the ESPVR has been shown to be relatively sensitive to changes in inotropic state (15,17,19,23), but evidence of nonlinearity (24)(25)(26)(27)(28) and afterload sensitivity (13,23,29,30) has been found.…”
mentioning
confidence: 99%
“…The methodological prerequisites for determining all of the essential parameters of mechanical cardiac action in situ have been available for a long time -and have been improved considerably during the last few years, although some detailed problems remain to be solved (5,7,12,57,59,63,64). However, beyond a merely descriptive presentation ( Fig.…”
mentioning
confidence: 99%